PENGUATAN NILAI SENI DAN BUDAYA SAWAT: Studi Sejarah Tari Tradisional di Pulau Ay-Banda - Kasman Renyaan; Varis Vadly Sanduan; Idul La Muhamad (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2026)
This article explains the strengthening of artistic and cultural values ​​in the historical study of the Sawat Dance as a traditional artistic heritage of the Ay Island community, Banda Naira. The Sawat Dance is performed in various traditional activities, welcoming honored guests, formal events at educational institutions, as well as cultural and tourism performances. This study aims to trace the historical roots of the Sawat Dance on Ay Island, understand the educational process for the younger generation, and examine efforts to preserve it amidst social changes in society. The study used a qualitative method with an ethnohistorical study approach. Data were obtained through Focus Group Discussions (FGDs), interviews, participatory observation, literature studies, and video documentation. Data were analyzed descriptively qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results show that the Sawat Dance on Ay Island is rooted in the Sawat art tradition in East Seram, which has existed since the 1960s and began to be taught to the younger generation in the 1970s. Although some people consider it an original art from Ay Island, the Sawat Dance is not found in other villages in the Banda Islands, making it a cultural identity of the local community. Over time, the Sawat Art of Ay Island has evolved into two variations: the Regular Sawat and the Dayung Sawat. The Dayung Sawat reflects the maritime culture of the Ay Island community as a seafaring society. Strengthening of artistic and cultural values ​​is carried out through practice-based education and intergenerational transmission within families and communities. The preservation of the Sawat Dance is also supported by schools, traditional leaders, cultural performances, and tourism activities in Banda Naira. The Sawat Dance not only serves as a medium for cultural inheritance but also strengthens social identity, provides economic value through tourism activities, and maintains the collective memory of the Ay Island community.